Analisis Pengaruh Return On Assets, Sales Growth Dan Leverage Terhadap Tax Avoidance - Hasanah, Rizki; Jusmani, Jusmani; Lilianti, Emma (Gorontalo Accounting Journal, 2024)
This research aims to obtain empirical evidence regarding the effect of return on assets, sales growth and leverage on tax avoidance. This research method uses quantitative descriptive analysis techniques in the analysis process using descriptive statistical techniques, classical assumption test analysis, multiple regression analysis, coefficient of determination test, t test and F test assisted by SPSS 25. The results of the study concluded partially that sales growth has a significant effect on tax avoidance, while return on assets and leverage have no significant effect on tax avoidance. Simultaneous testing shows the results of return on assets, sales growth and leverage have a significant effect on tax avoidance.